The Caring Hand that Cripples: The East German Labor Market after Reunification - Snower, Dennis J; Merkl, Christian (American Economic Review, 2006)
The Caring Hand that Cripples: The East German Labor Market after Reunification by Dennis J. Snower and Christian Merkl. Published in volume 96, issue 2, pages 375-382 of American Economic Review, May 2006